NORTHWEST SVALBARD DURING THE LAST GLACIATION: ICE-FREE AREAS EXISTED - Landvik J.Y.; Brook E.J.; Gualtieri L.; Raisbeck G. (My University, 2003)
The possibility that ice-free areas existed during the late Weichselian glaciation of the Svalbard archipelago has been debated for several decades. This study reveals the first geologic evidence that nunataks existed on the islands of northwest Svalbard. Several 10Be exposure ages were obtained from bedrock and glacial erratics on Dansk and Amsterdam Islands. Exposure ages for glacial erratics laid down in block-field-covered plateaus >300 m above sea level show that the last ice sheet that completely covered the islands deglaciated >80 k.y. ago. Dating of marine sediments close to sea level reveals that full ice-free conditions were achieved by ca. 50 ka. During the late Weichselian, the coastal lowlands were glaciated, and the major fjords and troughs controlled glacier flow. The existence of nunataks at this time opens the possibility for glacial survival of plant species. [PUBLICATION ABSTRACT]
Keywords: Svalbard; Weichselian; Last Glacial Maximum; exposure age; nunataks